2004
DOI: 10.1002/adma.200306281
|View full text |Cite
|
Sign up to set email alerts
|

Facile Creation of a Super‐Amphiphobic Coating Surface with Bionic Microstructure

Abstract: In nature, there are vast singular structures or morphologies on biological surfaces that exhibit super-water-repellent properties. [1,2] The two-length-scaled hierarchical structure of the surface of the sacred lotus leaf is a good example. [3] In the meantime, the wetting ability of liquids on solid surfaces has become very important in daily life as well as in many industrial processes. Super-hydrophobic surfaces and super-amphiphobic surfacesÐi.e., surfaces that exhibit both water-repellent and oil-repelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
266
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 382 publications
(271 citation statements)
references
References 21 publications
2
266
1
2
Order By: Relevance
“…in which f is the fraction of the solid/liquid interface, while (1 À f) is that of the air/liquid interface, indicates that, when a rough surface, which possesses nano structures 30 or micro/nano hierarchical structures, 33 comes into contact with liquid, air may be trapped in the rough area. The trapped air layer will contribute greatly to repel the liquid.…”
Section: Rough Structurementioning
confidence: 99%
See 2 more Smart Citations
“…in which f is the fraction of the solid/liquid interface, while (1 À f) is that of the air/liquid interface, indicates that, when a rough surface, which possesses nano structures 30 or micro/nano hierarchical structures, 33 comes into contact with liquid, air may be trapped in the rough area. The trapped air layer will contribute greatly to repel the liquid.…”
Section: Rough Structurementioning
confidence: 99%
“…107 Other Methods One-Step Casting Process Utilizing Difference in Solubility of Polymers Xie et al reported a superoleophobic PMMA and fluorineend-capped polyurethane film. 33 This film was fabricated by utilizing difference in solubility of the two polymers in one solvent. The SEM image showed the polymer surfaces possess natural lotus-like micro/nano structures [ Fig.…”
Section: Coating Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, researchers have made impressive efforts to prepare superhydrophobic surfaces for potential applications in a variety of areas [1][2][3][4][5][6][7][8]. Among others, superhydrophobic textiles have been successfully obtained by a number of different approaches [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…No natural surface can show that it is greater than 150° of the static contact angle and below 10° of the rolling angle at the same time for water and organic liquid. Such surface is superhydrophobic and superoleophobic [13,14].…”
Section: Introductionmentioning
confidence: 99%